Democratic audit: towards a broader view of democratic achievement - Beetham, David et al. (2003)
How democratic is Britain? Using data collected by Democratic Audit, this article argues that Britain's progress towards democracy has been uneven in 2002. It assesses a wide range of areas, including the state of civil and political rights, the promotion of economic and social rights, elections and voter participation, party democracy, the effectiveness and responsiveness of government, the role of women in public life, devolution, and the state of civil society. The authors conclude that the major lesson to be learned is that democracy is a never-ending process and that a major weakness of New Labour's approach is that it is unfocused and lacks a clear definition and understanding of democratic principles. - Reproduced.
Keywords: Democracy - Great Britain; Democracy